Piezofluorochromism in Charge‐Transfer Inclusion Crystals: The Influence of High Pressure versus Mechanical Grinding. Issue 5 (26th April 2018) - Ono, Toshikazu; Tsukiyama, Yoshifumi; Taema, Ai; Sato, Hiroyasu; Kiyooka, Hidetoshi; Yamaguchi, Yuma; Nagahashi, Ayumi; Nishiyama, Manami; Akahama, Yuichi; Ozawa, Yoshiki; Abe, Masaaki; Hisaeda, Yoshio
Abstract: The front cover artwork is provided by the group of Prof. Y. Hisaeda at Kyushu University (Japan). The work is in collaboration with the group of Prof. M. Abe and Prof. Y. Akahama at University of Hyogo and Dr. H. Sato at Rigaku Corporation. The image shows multicolor piezofluorochromism in charge‐transfer crystals under high‐pressure using a diamond anvil cell. Read the full text of the Communication at10.1002/cptc.201700227 . Abstract : "Luminescence charge‐transfer complexes showed reversible multichromism over the entire visible region in response to high pressure using a diamond anvil cell …" This and more about the story behind the front cover can be found in the Communication at10.1002/cptc.201700227 .